The influence of the pyrolysis process on mechanical parameters and tightness of the black glasses layers on titanium substrates. Issue 14 (1st October 2017) - Gawęda, M.; Długoń, E.; Leśniak, M.; Kurpaska, Ł.; Simka, W.; Sowa, M.; Sitarz, M.
Abstract: Black glasses are amorphous materials in which structure Si–O bonds coexist with Si–C bonds. The substitution of divalent oxygen ions by tetravalent carbon ions causes the change of properties, especially mechanical ones. The materials were obtained from the sol-gel synthesized ladder-like polysilsesquioxane organosilicon precursors. After deposition on titanium substrates and ceramization, continuous and hermetic layers were obtained. Adhesion, Young's modulus, hardness, roughness and corrosion resistance were examined as the most relevant mechanical properties of the obtained layers. Nanoindentation, surface mapping, electrochemical, SEM and confocal microscope measurements results are discussed in relation to the pyrolysis temperature of the black glasses layers.